Exogenous application of polyamines improves shelf life and fruit quality of mango - Malik, Aman; Singh, Zora; Tan, S. (International Society Horticultural Science, 2006)
This research aimed to investigate the benefit of postharvest application of polyamines {Spermine (SPM), Spermidine (SPD) and Putrescine (PUT)} on the shelf life and fruit quality of mango (Mangifera indica L. cv Kensington Pride). Polyamine application retarded fruit softness, colour development and reduced physiological weight loss during storage without a significant reduction in ethylene production. Lower concentrations of SPM (0.01 mM), and higher concentrations of SPD (0.5 mM) and PUT (1 mM) were more effective in retarding fruit softening. During fruit ripening, SPM (0.01 mM) exhibited the minimum respiration compared with the control fruit. Analysis of ripe fruit, which were stored for 3 or 4 weeks, showed that polyamine application significantly increased fruit firmness, acidity, ascorbic acid, while reducing the TSS/acid ratio and total carotenoid content compared with the control. The exogenous application of polyamines improved shelf life of mango without having deleterious effect on fruit quality.